2008
DOI: 10.1155/2008/305403
|View full text |Cite
|
Sign up to set email alerts
|

Phlorizin Prevents Glomerular Hyperfiltration but not Hypertrophy in Diabetic Rats

Abstract: The relationships of renal and glomerular hypertrophies to development of hyperfiltration and proteinuria early in streptozotocin-induced diabetes were explored. Control, diabetic, phlorizin-treated controls, and diabetic male Fischer rats were used. Phlorizin (an Na+-glucose cotransport inhibitor) was given at a dose sufficient to normalize blood glucose. Inulin clearance (Cinulin) and protein excretion rate (PER) were measured. For morphometry, kidney sections were stained with periodic acid Schiff. At one w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
82
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(94 citation statements)
references
References 39 publications
8
82
3
1
Order By: Relevance
“…Previous experimental work using different animal models of kidney disease have demonstrated that SGLT2 inhibition alleviates renal damage. In Akita and streptozotocin-induced animal models of insulin-deficient diabetes, SGLT2 inhibition reduced albuminuria [18][19][20]. SGLT2 inhibition has similar anti-albuminuric effects in animal models of type 2 diabetes [21], including recent evidence that empagliflozin reduced albuminuria, independent of effects on BP or hyperglycaemia, in BTBR ob/ob mouse models of type 2 diabetes [22].…”
Section: Discussionmentioning
confidence: 94%
“…Previous experimental work using different animal models of kidney disease have demonstrated that SGLT2 inhibition alleviates renal damage. In Akita and streptozotocin-induced animal models of insulin-deficient diabetes, SGLT2 inhibition reduced albuminuria [18][19][20]. SGLT2 inhibition has similar anti-albuminuric effects in animal models of type 2 diabetes [21], including recent evidence that empagliflozin reduced albuminuria, independent of effects on BP or hyperglycaemia, in BTBR ob/ob mouse models of type 2 diabetes [22].…”
Section: Discussionmentioning
confidence: 94%
“…A previous study suggested that phlorizin, a SGLT inhibitor and not a selective SGLT2 inhibitor, had an inhibitory effect on the tubular reabsorption of β2-microglobulin in control and diabetic rats [33]. It might be that ipragliflozin similarly affected the tubular reabsorption of β2-microglobulin.…”
Section: Discussionmentioning
confidence: 95%
“…The renal hypertrophy of the diabetic control rats suggests their progression to the development of renal pathology [16] while the decrease in the relative kidney weights of the diabetic rats fed unripe plantain suggests the ability of unripe plantain to ameliorate renal hypertrophy.…”
Section: Discussionmentioning
confidence: 99%